2023
DOI: 10.3390/cells12050756
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Expression Profiles of Mouse Round Spermatids in GRTH/DDX25-Mediated Spermiogenesis: mRNA–miRNA Network Analysis

Abstract: GRTH/DDX25 is a testis-specific DEAD-box family of RNA helicase, which plays an essential role in spermatogenesis and male fertility. There are two forms of GRTH, a 56 kDa non-phosphorylated form and a 61 kDa phosphorylated form (pGRTH). GRTH-KO and GRTH Knock-In (KI) mice with R242H mutation (lack pGRTH) are sterile with a spermatogenic arrest at step 8 of spermiogenesis due to failure of round spermatids (RS) to elongate. We performed mRNA-seq and miRNA-seq analysis on RS of WT, KI, and KO to identify crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Recent research suggests that LIAS may play a critical role in spermatogenesis, as it was shown to be downregulated in cases of spermatogenic dysfunction in humans ( Zhao et al, 2023 ). The UBE2K gene encodes a protein that is a member of the ubiquitin-conjugating enzyme family and is crucial for the ubiquitination pathways, which are essential to the later stages of spermatid development during spermiogenesis ( Anbazhagan et al, 2023 ). Malfunctions in the ubiquitination system can impair sperm development, ultimately resulting in male infertility ( Nakamura, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that LIAS may play a critical role in spermatogenesis, as it was shown to be downregulated in cases of spermatogenic dysfunction in humans ( Zhao et al, 2023 ). The UBE2K gene encodes a protein that is a member of the ubiquitin-conjugating enzyme family and is crucial for the ubiquitination pathways, which are essential to the later stages of spermatid development during spermiogenesis ( Anbazhagan et al, 2023 ). Malfunctions in the ubiquitination system can impair sperm development, ultimately resulting in male infertility ( Nakamura, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-34bc - / - ;449 - / - mice exhibit a decrease in the proportion of spermatozoa, elongating spermatids, and abnormalities in sperm morphology with the separation of spermatozoa heads and tails ( 11 ). In one study, miR-32, miR-184, miR-335, miR-140, miR-141, miR-1981, miR-202, miR-880, and miR-669c were downregulated in both KO and KI mice, whereas miR-150, miR-196a-2, miR-652, miR-146, miR-10b, miR-379, miR-122a, miR-26a, miR-27a, miR-127, and miR-328 were upregulated in both KO and KI mice and negatively regulated spermatid differentiation ( 117 ). Liu et al.…”
Section: Mechanism Of Mirna Involved In Spermatogenesismentioning
confidence: 99%
“…59 DDX25 was also shown to affect the expression levels of other miRNAs in addition to miR-469; therefore, it appears to have a broader role in the control of miRNA-mRNA networks to support haploid differentiation of spermatids. 60 Another miRNA, miR-122a, that is expressed in late stages of male germ cells differentiation has also been shown to directly control TNP2 expression by inducing mRNA cleavage. 61…”
Section: Expression and Function Of Mirnas During Spermatogenesismentioning
confidence: 99%